2010
DOI: 10.1007/s00203-010-0543-2
|View full text |Cite
|
Sign up to set email alerts
|

Mixture of endophytic Agrobacterium and Sinorhizobium meliloti strains could induce nonspecific nodulation on some woody legumes

Abstract: Agrobacterium sp. II CCBAU 21244 isolated from root nodules of Wisteria sinensis was verified as an endophytic bacterium by inoculation and reisolation tests. However, inoculation with a mixture of this strain and a Sinorhizobium meliloti strain could induce root nodules on W. sinensis and two other woody legumes, which do not form a symbiosis with S. meliloti alone. Rod-shaped and irregular nodules were found on the inoculated plants, in which the S. meliloti strain was detected in all of the nodules; while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…CT5. These species have already been reported as endophytes of many plants (Goryluk et al 2009;Khan and Doty 2009;Ma et al 2009;Liu et al 2010;Rashid et al 2012). Endophytes like Bacillus subtilis, Bacillus sp., and Pseudomonas putida are known for their ability to produce indole acetic acid (IAA) (Khan and Doty 2009;He et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…CT5. These species have already been reported as endophytes of many plants (Goryluk et al 2009;Khan and Doty 2009;Ma et al 2009;Liu et al 2010;Rashid et al 2012). Endophytes like Bacillus subtilis, Bacillus sp., and Pseudomonas putida are known for their ability to produce indole acetic acid (IAA) (Khan and Doty 2009;He et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, many Agrobacterium strains have been isolated from root nodules of legume plants and though most were non-symbiotic belonging to Agrobacterium tumefaciens, some may represent novel biovars (19). Moreover, Velazquez et al (39) reported for the first time the occurrence of two strains (163C and ATCC 11325 T ) belonging to R. rhizogenes able to nodulate Phaseolus vulgaris.…”
mentioning
confidence: 99%
“…Belonging to this bacterial phylum, Bradyrhizobium, Rhizobium and Sinorhizobium lineages were detected as main endophytes (Tables 2 and 4). Previously, existence of endophytic Rhizobium radiobacter (=Agrobacterium tumefaciens) strains in nodules or roots of many legumes and their interaction with symbiotic bacteria have been studied (Liu et al 2010;Mrabet et al 2006), but the existence of symbiotic bacteria as endophytes in the same host plant has not been well studied. It was interesting that the inoculated B. liaoningense strain occupied 75% and 80% of the nodules at stage R2 in the treatments of MSR and ISR, respectively, but its abundance as root endophyte was less than that of Sinorhizobium.…”
Section: Discussionmentioning
confidence: 99%